2018
DOI: 10.1093/jlb/lsy022
|View full text |Cite
|
Sign up to set email alerts
|

May your drug price be evergreen

Abstract: Presenting the first comprehensive study of evergreening, this article examines the extent to which evergreening behavior—which can be defined as artificially extending the protection cliff—may contribute to the problem. The author analyses all drugs on the market between 2005 and 2015, combing through 60,000 data points to examine every instance in which a company added a new patent or exclusivity. The results show a startling departure from the classic conceptualization of intellectual property protection fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 0 publications
0
48
0
2
Order By: Relevance
“…“Pay‐for‐delay” is one tactic used by drug makers to extend the period of exclusivity by offering cash or a non‐cash benefit to generic competitors in exchange for delaying their entry into the market; this dubious practice has been eyed by policy‐makers as one potential target to bring down drug prices 20 . “Evergreening” is the technique of applying for new patents to a drug (sometimes repeatedly) after making perfunctory and clinically meaningless changes to the drug that nevertheless qualify as new intellectual property 21 . In these situations, the additional market exclusivity afforded to the drugs is unmerited.…”
Section: Brand Name and Generic Drugsmentioning
confidence: 99%
“…“Pay‐for‐delay” is one tactic used by drug makers to extend the period of exclusivity by offering cash or a non‐cash benefit to generic competitors in exchange for delaying their entry into the market; this dubious practice has been eyed by policy‐makers as one potential target to bring down drug prices 20 . “Evergreening” is the technique of applying for new patents to a drug (sometimes repeatedly) after making perfunctory and clinically meaningless changes to the drug that nevertheless qualify as new intellectual property 21 . In these situations, the additional market exclusivity afforded to the drugs is unmerited.…”
Section: Brand Name and Generic Drugsmentioning
confidence: 99%
“…Gaudry (2011) notes that drugs approved by the FDA toward the latter end of the 2000-2010 period were more likely to be evergreened with three years of exclusivity than they were at the beginning of the decade. Similarly, Feldman (2017) shows that the probability of an existing drug receiving a new patent doubled between 2005 and 2015. Hemphill and Sampat (2012) only for drugs administered in a medical setting or through some alternative arrangement (like some Medigap and Medicare Advantage plans), leaving many seniors uninsured for outpatient 16 Alkhafaji et al (2012) notes that a high market share of citalopram/escitalopram went to branded escitalopram, even though a generic version of citalopram was available.…”
Section: Evergreeningmentioning
confidence: 99%
“…17 For a study comparing efficacy in an original versus an evergreened version of a product, see Alkhafaji et al (2012), which found limited evidence that the evergreened version of citalopram was an improvement. For a paper suggesting that this practice does little to advance patient care and instead represents gaming by pharmaceutical companies, see Feldman (2017). 18 Hemphill and Sedat (2015) suggests that evergreening may not prevent generic entry, in which case any impact on drug prices would come through the maintenance of brand share.…”
Section: Evergreeningmentioning
confidence: 99%
“…Competition may be held in abeyance, but those who receive the benefit of a patent or exclusivity must pay for that privilege by disclosing sufficient information such that competitors will be able to step into the market." 83 Patent law's notion of competition, however, is quite different from that of antitrust law. Antitrust is concerned with the clash of the mighty.…”
Section: B the Proper Use Of Patent Power: Restraining Competition Wmentioning
confidence: 99%